Le fonti del vocabolario teologico delle Epistole dello pseudo-Dionigi Areopagita - Nicolò Sassi (Lexicon Philosophicum)
What reveals the language of the corpus Areopagiticum that we can use to determine its origin? Is it possible to detect specific words or lexical clusters which help situate the Sitz im Leben of the corpus within a specific theological school or movement? This study investigates these questions: through an analysis of pseudo-Dionysius’ vocabulary and syntagmata in the Epistulae, this study will trace the theological sources that shaped and nurtured pseudo-Dionysius’ thought.